PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA TOUR AND TRAVEL PADA PT. SAKINAH TOUR & TRAVEL DI JAKARTA SELATAN - Amellia, Amellia; Ida Zuniarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to analyze the influence of service quality and price on consumer decisions at PT. Sakinah Tour & Travel in South Jakarta. The issue addressed in this research is the decline in the number of umrah pilgrims post-Covid-19, attributed to dissatisfaction with service quality and pricing. The sampling technique used in this study is Slovin's formula, with a sample size of 60 respondents. The results indicate that both service quality and price have a positive and significant effect on consumer decisions, with Thitung values of 6.317 and 5.530, respectively. These findings emphasize the importance of improving service quality and setting competitive prices to attract more consumers.